Silicon anode for use in electrochemical cells - Patent Application 20070123633
A composite anode with nanostructured silicon and a solid electrolyte addresses volume change issues in lithium-ion batteries, enhancing first-cycle efficiency and cycle life through a branched particle morphology that limits side reactions.
Patent Information
- Application Number
- JP2024539668
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-30
- Filing Date
- 2022-12-30
- Publication Date
- 2025-01-17
AI Technical Summary
Carbon-based anodes in lithium-ion batteries face challenges due to volume changes associated with lithium alloying, leading to cracking and reduced cycle life, making them unsuitable for high-capacity applications.
A composite anode comprising silicon or its alloy, a solid electrolyte, and a binder, with nanostructured silicon having a branched particle morphology and low surface area, which limits side reactions and maintains structural integrity during lithium insertion and extraction.
The composite anode exhibits high first-cycle efficiency and long cycle life, enabling high-capacity lithium-ion batteries with improved coulombic efficiency and reduced capacity loss.
Smart Images

Figure 2025501267000001_ABST
Abstract
Description
[Technical field]
[0001] Various aspects described herein relate to the field of solid state primary and secondary electrochemical cells, electrodes, and electrode materials, and corresponding methods of making and using same.
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application No. 63 / 295,291, filed December 30, 2021, entitled "Silicon Anodes for Solid-State Batteries," the entire contents of which are incorporated herein by reference. [Background technology]
[0003] Lithium-based rechargeable batteries are common for powering many forms of modern electronic devices and have the ability to serve as a power source for hybrid and fully electric vehicles. Modern lithium-based rechargeable batteries typically use carbon-based anodes to store lithium ions. In these anodes, the lithium ions are stored by being intercalated between the planes of carbon atoms that make up graphite particles. Carbon-based anodes have been tailored to provide acceptable performance in modern lithium-ion batteries. However, carbon-based anodes have reached maturity in their lithium-ion storage.
[0004] An alternative to carbon-based anodes is alloy-type anodes. In alloy-type anodes, lithium ions alloy with the active anode material rather than intercalating between the sheets of carbon in graphite particles. These materials can have up to ten times (10x) the lithium ion storage capacity compared to graphite anodes. Typical alloy-type anodes include silicon, tin, and aluminum, as well as more exotic materials such as germanium and gold. These alloy materials have their own advantages and disadvantages, such as cost, specific capacity, processability, and voltage penalty.
[0005] One of the challenges faced in these systems is the volume change associated with alloying lithium with the active material. For example, volume changes of around 400% can occur in some systems. The volume change can cause difficulties at the macro and micro levels. At the macro level, battery packs must accommodate expanding cells, and at the micro level, the continuous expansion and contraction of the active area can lead to cracks. And particles in the active area can lose electrical connection with their surrounding matrix and can also undergo undesirable side reactions between the fresh surfaces of the particles and the battery electrolyte.
[0006] Silicon (Si) is an example of an alloy-type anode material that can theoretically store more than 10 times the amount of lithium ions compared to graphite, has a modest voltage penalty, and is abundant and inexpensive in its bulk form. Unfortunately, the large (e.g., 400%) volume change of silicon-lithium alloys in conventional liquid electrolyte lithium-ion cells has hindered attempts to use silicon in the anode. As the material expands and contracts, cracks form and the exposed fresh surfaces of the cracks react to form new solid electrolyte interphases, which consume the electrolyte and the lithium source in the cell. Thus, the cell loses some of its capacity during each cycle and may eventually fail after several cycles.
[0007] Although advances have been made in the field of lithium batteries, there remains a need in the art for solid anodes that are more resistant to cracking and have improved coulombic efficiency. Summary of the Invention [Problem to be solved by the invention]
[0008] Provided herein is a composite anode for an electrochemical cell. [Means for solving the problem]
[0009] The composite anode composition generally includes silicon or an alloy thereof in an amount of at least about 30 wt % of the composite anode, a solid electrolyte material in an amount of about 0 wt % to about 40 wt % of the composite anode, and a binder in an amount of about 0 wt % to about 20 wt % of the composite anode. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 shows a plot comparing the cycle life of electrochemical cells made in Example 1, Comparative Example 1, and Comparative Example 2. [Diagram 2] FIG. 2 shows a plot comparing the cycle life of electrochemical cells made in Example 1, Example 2, and Comparative Example 3. [Diagram 3] FIG. 3 shows a plot comparing the cycle life of electrochemical cells made in Example 1 and Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In some embodiments, the silicon has a particle size of about 10 nm to about 100 nm. In an exemplary embodiment, the silicon has an average particle size of about 50 nm to about 80 nm.
[0012] In some embodiments, the silicon has a crystallite size of about 1 nm to about 50 nm. In exemplary embodiments, the silicon has a crystallite size of about 1 nm to about 20 nm.
[0013] In some embodiments, silicon is about 1 m 2 / g~about 50m 2 / g, or about 1m 2 / g~about 20m 2 In some additional embodiments, the silicon has a surface area of about 20 m 2 / g.
[0014] In some embodiments, silicon is present in an amount of about 30 wt% to about 98 wt% of the composite anode. In some additional embodiments, silicon is present in an amount of at least about 40 wt% of the composite anode.
[0015] In some embodiments, the silicon has a crystallite size to surface area ratio (nm:m) of about 1:50 to about 50:1. 2 / g). In some embodiments, the silicon has a crystallite size to particle size (nm:nm) ratio of about 1:300 to about 1:1. In still further embodiments, the silicon has a surface area to particle size (m 2 / g:nm).
[0016] In some embodiments, the composite anode further comprises a conductive additive in an amount of about 0 wt% to about 15 wt% of the composite anode. In some embodiments, the conductive additive comprises one or more of carbon fiber, graphite, graphene, carbon black, conductive carbon, amorphous carbon, VGCF, silicon-carbon composite, and carbon nanotubes. In some additional embodiments, the conductive additive has a particle size of about 5 nm to about 100 nm.
[0017] In some embodiments, the composite anode has a mass of about 1 g / cm 3 ~Approx. 1.75g / cm 3 has a density of
[0018] In some embodiments, the composite anode is made of tin, germanium, graphite, Li4Ti5O 12 , hard carbon, or a combination thereof.
[0019] 1. A composite anode composition comprising silicon or an alloy thereof in an amount of at least about 30 wt. % of the composite anode, a solid electrolyte material in an amount of about 0 wt. % to about 40 wt. % of the composite anode, and a binder in an amount of about 0 wt. % to about 20 wt. % of the composite anode, wherein the silicon has the following characteristics: a particle size of about 10 nm to about 100 nm, a crystallite size of about 1 nm to about 20 nm, and a binder content of about 100% to about 100% by weight of the composite anode.2 / g~about 20m 2 Further provided herein are composite anode compositions having one or more of:
[0020] In some embodiments, the silicon has a crystallite size to surface area ratio (nm:m) of about 1:50 to about 50:1. 2 / g). In some embodiments, the silicon has a crystallite size to particle size (nm:nm) ratio of about 1:300 to about 1:1. In still further embodiments, the silicon has a surface area to particle size (m 2 / g:nm).
[0021] 1. A composite anode composition comprising silicon or an alloy thereof in an amount of at least about 30 wt. % of the composite anode, a solid electrolyte material in an amount of about 0 wt. % to about 40 wt. % of the composite anode, and a binder in an amount of about 0 wt. % to about 20 wt. % of the composite anode, wherein the silicon has the following characteristics: a particle size of about 10 nm to about 100 nm, a crystallite size of about 1 nm to about 20 nm, and a binder content of about 100% to about 100% by weight of the composite anode. 2 / g~about 20m 2 Further provided herein are composite anode compositions having two or more of: a surface area of 0.1 to 1.0 nm / g.
[0022] In some embodiments, the silicon has a crystallite size to surface area ratio (nm:m) of about 1:50 to about 50:1. 2 / g). In some embodiments, the silicon has a crystallite size to particle size (nm:nm) ratio of about 1:300 to about 1:1. In still further embodiments, the silicon has a surface area to particle size (m 2 / g:nm).
[0023] 1. A composite anode composition comprising silicon or an alloy thereof in an amount of at least about 30 wt. % of the composite anode, a solid electrolyte material in an amount of about 0 wt. % to about 40 wt. % of the composite anode, and a binder in an amount of about 0 wt. % to about 20 wt. % of the composite anode, wherein the silicon has the following characteristics: a particle size of about 10 nm to about 100 nm, a crystallite size of about 1 nm to about 20 nm, and a binder content of about 100% to about 100% by weight of the composite anode. 2 / g~about 20m 2 Further provided herein is a composite anode composition having a surface area of 0.1 μm / g.
[0024] In some embodiments, the silicon has a crystallite size to surface area ratio (nm:m) of about 1:50 to about 50:1. 2 / g). In some embodiments, the silicon has a crystallite size to particle size (nm:nm) ratio of about 1:300 to about 1:1. In still further embodiments, the silicon has a surface area to particle size (m 2 / g:nm).
[0025] Further provided herein is an electrochemical cell. The electrochemical cell generally includes a composite anode, a cathode, and an electrolyte layer. The composite anode includes silicon or an alloy thereof in an amount of at least about 30 wt% of the composite anode, a solid electrolyte material in an amount of about 0 wt% to about 40 wt% of the composite anode, and a binder in an amount of about 0 wt% to about 20 wt% of the composite anode.
[0026] In some embodiments, the silicon has a particle size of about 10 nm to about 100 nm. In an exemplary embodiment, the silicon has an average particle size of about 50 nm to about 80 nm.
[0027] In some embodiments, the silicon has a crystallite size of about 1 nm to about 50 nm. In exemplary embodiments, the silicon has a crystallite size of about 1 nm to about 20 nm.
[0028] In some embodiments, silicon is about 1 m 2 / g~about 50m 2 / g, or about 1m2 / g~about 20m 2 In some additional embodiments, the silicon has a surface area of about 20 m 2 / g.
[0029] In some embodiments, silicon is present in an amount of about 30 wt% to about 98 wt% of the composite anode. In some additional embodiments, silicon is present in an amount of at least about 40 wt% of the composite anode.
[0030] In some embodiments, the silicon has a crystallite size to surface area ratio (nm:m) of about 1:50 to about 50:1. 2 / g). In some embodiments, the silicon has a crystallite size to particle size (nm:nm) ratio of about 1:300 to about 1:1. In still further embodiments, the silicon has a surface area to particle size (m 2 / g:nm).
[0031] In some embodiments, the composite anode further comprises a conductive additive in an amount of about 0 wt% to about 15 wt% of the composite anode. In some embodiments, the conductive additive comprises one or more of carbon fiber, graphite, graphene, carbon black, conductive carbon, amorphous carbon, VGCF, silicon-carbon composite, and carbon nanotubes. In some additional embodiments, the conductive additive has a particle size of about 5 nm to about 100 nm.
[0032] In some embodiments, the composite anode has a mass of about 1 g / cm 3 ~Approx. 1.75g / cm 3 has a density of
[0033] In some embodiments, the composite anode is made of tin, germanium, graphite, Li4Ti5O 12 , hard carbon, or a combination thereof.
[0034] In some embodiments, the cathode comprises a cathode active material. In some embodiments, the cathode comprises a conductive additive. In some embodiments, the cathode comprises a solid electrolyte.
[0035] In some embodiments, the electrolyte layer comprises a solid electrolyte. In some additional embodiments, the electrolyte layer comprises a binder. In some embodiments, the electrolyte layer is disposed between the composite anode and the cathode.
[0036] In some embodiments, the electrochemical cell further comprises a first current collector and a second current collector. In some aspects, the first current collector is disposed adjacent to the composite anode. In some additional aspects, the second current collector is disposed adjacent to the cathode.
[0037] Further provided herein is a method for preparing a composite anode for an electrochemical cell. The method includes combining silicon or its alloy, a solid electrolyte material, and a binder to form a composite mixture, adding a solvent to the composite mixture to form a slurry, casting the slurry on a substrate, and drying the slurry on the substrate to form a composite anode. In some embodiments, the method further includes densifying the composite anode.
[0038] In some embodiments, the silicon has a particle size of about 10 nm to about 100 nm. In an exemplary embodiment, the silicon has an average particle size of about 50 nm to about 80 nm.
[0039] In some embodiments, the silicon has a crystallite size of about 1 nm to about 50 nm. In exemplary embodiments, the silicon has a crystallite size of about 1 nm to about 20 nm.
[0040] In some embodiments, silicon is about 1 m 2 / g~about 50m 2 / g, or about 1m 2 / g~about 20m 2In some additional embodiments, the silicon has a surface area of about 20 m 2 / g.
[0041] In some embodiments, silicon is present in an amount of about 30 wt% to about 98 wt% of the composite anode. In some additional embodiments, silicon is present in an amount of at least about 40 wt% of the composite anode.
[0042] In some embodiments, the silicon has a crystallite size to surface area ratio (nm:m) of about 1:50 to about 50:1. 2 / g). In some embodiments, the silicon has a crystallite size to particle size (nm:nm) ratio of about 1:300 to about 1:1. In still further embodiments, the silicon has a surface area to particle size (m 2 / g:nm).
[0043] In some embodiments, the composite mixture further comprises a conductive additive in an amount of about 0% to about 15% by weight of the composite anode. In some embodiments, the conductive additive comprises one or more of carbon fiber, graphite, graphene, carbon black, conductive carbon, amorphous carbon, VGCF, silicon-carbon composite, and carbon nanotubes. In some additional embodiments, the conductive additive has a particle size of about 5 nm to about 100 nm.
[0044] In some embodiments, the composite anode has a mass of about 1 g / cm 3 ~Approx. 1.75g / cm 3 has a density of
[0045] In some embodiments, the composite mixture is made of tin, germanium, graphite, L i4 Ti5O 12 , hard carbon, or a combination thereof.
[0046] The present disclosure can be understood by reference to the following detailed description in conjunction with the drawings, which are briefly described below.
[0047] It should be noted that for clarity of illustration, certain elements in the drawings may not be drawn to scale.
[0048] Detailed Description In the following description, specific details are provided to provide a thorough understanding of the various aspects of the present disclosure. Upon reading and understanding this specification, claims, and drawings, those skilled in the art will understand that some embodiments may be implemented without paying attention to some of the specific details described herein. Furthermore, in order to avoid obscuring the present disclosure, some known methods, processes, devices, and systems utilized in the various aspects described herein are not disclosed in detail.
[0049] The inventors have surprisingly found that nanostructured silicon, composed of branched particles with low surface area, exhibits very high first cycle efficiency when integrated into a solid electrolyte. As used herein, "branched particles" refers to particles that contain three or more primary particles in series. As used herein, "primary particles" refers to individual granules in a powder material. Each primary particle may contain one or more crystallites. Crystallites, as used herein, refer to individual crystals that form a primary particle. Two or more primary particles may aggregate to form a secondary particle. Due to the low surface area, only a small amount of silicon requires passivation by side reactions. Furthermore, the branched structure creates a porous structure, making it difficult for the solid electrolyte material to directly contact the silicon. Because the solid electrolyte is not mobile, silicon surfaces that are not initially in contact with the electrolyte will not react with the electrolyte.
[0050] The porous branched and coarse network of nanostructured silicon can also anchor itself to the surrounding composite matrix to create a mechanically robust structure as measured by anode cohesion. Without wishing to be bound by theory, silicon powders with higher surface areas tend to have lower anode cohesion and may require more binder to maintain structural integrity. The formation of a strong interface facilitates lithium transport to the silicon particles, which remain anchored within the network. Additionally, the voids within the branched network allow room for the silicon to expand, which explains the high capacity of this particular silicon morphology. With this silicon structure in a solid electrolyte, there is a limited amount of side reactions that can occur, voids exist to accommodate silicon expansion, and the particles remain tightly anchored in the composite matrix. The net effect is a very high first cycle efficiency, resulting in high capacity and long cycle life.
[0051] Nanoscale silicon also has a low surface area. The low surface area and small particle size lead to the formation of aggregates or chains that provide structural support to the silicon anode.
[0052] Nanoscale silicon also has a small crystallite size. As previously mentioned, crystallites are the individual crystals that form the primary particles of silicon. The small crystallite size and low surface area of silicon results in electrochemical cells with increased cell performance compared to cells using silicon with small crystallite size and high surface area as well as cells using silicon with large crystallite size and low surface area. The small crystallite size of silicon used herein reduces cracking of individual particles and potential loss of active material. The small crystallite size and low surface area of certain morphologies are more effective at preventing harmful Li ions that tend to form when silicon is fully lithiated. 15This prevents silicon from forming the Si4 phase. Additionally, the use of small crystallite size and low surface area Si material allows for increased processability by allowing the composite to be mixed into a slurry with ideal rheological properties for casting / coating. These properties include high solids loading allowing for the use of less solvent, reduced drying time of the cast layer, and slurry stability, thereby providing a longer time frame for performing casting and / or coating.
[0053] Preferably, the composite anode of the present disclosure contains less than 10 wt. % Li after lithiation in an electrochemical cell. 15 For example, the composite anode of the present disclosure contains less than 10 wt. % LiSi4 after lithiation in an electrochemical cell. 15 Si4, less than 9% by weight Li 15 Si4, less than 8 wt% Li 15 Si4, less than 7 wt% Li 15 Si4, less than 6 wt% Li 15 Si4, less than 5% by weight Li 15 Si4, less than 4 wt% Li 15 Si4, less than 3 wt% Li 15 Si4, less than 2% by weight Li 15 Si4 or less than 1% by weight Li 15 It may also include Si4.
[0054] High first cycle efficiency is beneficial in enabling long-life lithium-ion batteries.
[0055] In a cell with a lithium-containing cathode and an initially lithium-free anode, the cathode contains cyclable lithium available to the cell. During the first charge of the cell, lithium is removed from the cathode and reacts with the active components of the anode. Some of the lithium may be lost to undesirable side reactions in this process. Furthermore, upon discharge, some lithium may be trapped in the ionically or electrically isolated active components due to cracking or separation caused by volume changes. This lithium loss reduces the capacity of the cell and decreases the cycle life.
[0056] In some embodiments, the composite anode can have a thickness of about 1 μm to about 100 μm. In some aspects, the composite anode can have a thickness of about 1 μm to about 10 μm, about 1 μm to about 20 μm, about 1 μm to about 30 μm, about 1 μm to about 40 μm, about 1 μm to about 50 μm, about 1 μm to about 60 μm, about 1 μm to about 70 μm, about 1 μm to about 80 μm, about 1 μm to about 90 μm, about 10 μm to about 100 μm, about 20 μm to about 100 μm, or about 30 μm to about 40 μm. The anode may have a thickness of about 1 μm, about 30 μm to about 100 μm, about 40 μm to about 100 μm, about 50 μm to about 100 μm, about 60 μm to about 100 μm, about 70 μm to about 100 μm, about 80 μm to about 100 μm, about 90 μm to about 100 μm, about 10 μm to about 50 μm, about 20 μm to about 40 μm, or about 20 μm to about 30 μm. In some additional aspects, the anode may have a thickness of about 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, or about 100 μm. In an exemplary embodiment, the composite anode has a thickness of about 20 μm to about 30 μm.
[0057] The anode active material comprises silicon having an average particle size of less than about 1000 nm. As used herein, "silicon" refers to silicon metal or its alloys. Despite the difficulty in describing the particle size of silicon as discussed above, the average particle size of silicon (i.e., D 50) can be described. As used herein, "particle size" refers to the diameter of the primary particles of silicon. In some embodiments, the silicon may have an average particle size of less than 500 nm, less than 450 nm, less than 400 nm, less than 350 nm, less than 300 nm, less than 250 nm, less than 200 nm, less than 150 nm, or less than 100 nm. In some examples, the silicon has an average particle size of about 100 nm. The silicon may have a particle size of about 1 nm to about 25 nm, about 1 nm to about 50 nm, about 1 nm to about 75 nm, about 1 nm to about 100 nm, about 1 nm to about 125 nm, about 1 nm to about 150 nm, about 25 nm to about 150 nm, about 50 nm to about 150 nm, about 75 nm to about 150 nm, about 100 nm to about 150 nm, or about 125 nm to about 150 nm. In an exemplary embodiment, the silicon has an average particle size of about 50 nm to about 80 nm.
[0058] Silicon is about 1m 2 / g~about 100m 2 In some embodiments, the silicon can have a surface area of about 1 m 2 / g~about 10m 2 / g, approx. 1m 2 / g~about 20m 2 / g, approx. 1m 2 / g ~ approx. 30m 2 / g, approx. 1m 2 / g~about 40m 2 / g, approx. 10m 2 / g~about 50m 2 / g, approx. 10m 2 / g~about 60m 2 / g, approx. 10m 2 / g~about 70m 2 / g, approx. 10m 2 / g~about 80m 2 / g, approx. 10m 2 / g~about 90m 2 / g, approx. 10m 2 / g~about 100m 2 / g, about 20m 2 / g~about 100m 2 / g, approx. 30m 2 / g~about 100m 2 / g, approx. 40m 2 / g~about 100m2 / g, approx. 50m 2 / g~about 100m 2 / g, approx. 60m 2 / g~about 100m 2 / g, approx. 70m 2 / g~about 100m 2 / g, approx. 80m 2 / g~about 100m 2 / g, approx. 90m 2 / g~about 100m 2 / g, approx. 10m 2 / g~about 40m 2 / g, about 20m 2 / g~about 40m 2 In some examples, the silicon may have a surface area of about 30 m 2 In some additional examples, silicon has a surface area of about 20 m 2 / g.
[0059] The silicon can have a crystallite size of about 1 nm to about 50 nm. The crystallite size can be determined by applying the Scherrer equation or Rietveld refinement to the XRD pattern, as known to those skilled in the art. In some embodiments, the silicon can have a crystallite size of about 1 nm to about 5 nm, about 1 nm to about 10 nm, about 1 nm to about 20 nm, about 1 nm to about 30 nm, about 1 nm to about 40 nm, about 1 nm to about 50 nm, about 5 nm to about 50 nm, about 10 nm to about 50 nm, about 20 nm to about 50 nm, about 30 nm to about 50 nm, about 40 nm to about 50 nm, about 10 nm to about 40 nm, about 10 nm to about 30 nm, about 10 nm to about 20 nm, about 20 nm to about 40 nm, or about 30 nm to about 40 nm. In some examples, the silicon may have a crystallite size of about 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, 31 nm, 32 nm, 33 nm, 34 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm, 40 nm, 41 nm, 42 nm, 43 nm, 44 nm, 45 nm, 46 nm, 47 nm, 48 nm, 49 nm, or about 50 nm.
[0060] The silicon in the composite anode has a crystallite size to surface area (nm:m) ratio of about 1:50 to about 50:1. 2For example, the ratio of crystallite size to surface area may be about 1:50 to about 1:25, about 1:50 to about 1:10, about 1:50 to about 1:5, about 1:50 to about 1:2, about 1:50 to about 1:1, about 1:50 to about 2:1, about 1:50 to about 5:1, about 1:50 to about 10:1, about 1:50 to about 25:1, about 1:50 to about 50:1, about 1:25 to about 50:1, about 1:10 to about 50:1, about 1:5 to about 50:1, about 1:2 to about 50:1, about 1:1 to about 50:1, about 2:1 to about 50:1, about 5:1 to about 50:1, about 10:1 to about 50:1, or about 25:1 to about 50:1. The crystallite size to surface area ratio can be about 1:50, 1:40, 1:30, 1:20, 1:10, 1:5, 1:2, 1:1, 2:1, 5:1, 10:1, 20:1, 30:1, 40:1, or about 50:1. In an exemplary embodiment, the crystallite size to surface area ratio can be about 1:1. In another exemplary embodiment, the crystallite size to surface area ratio can be about 1:2.
[0061] The silicon in the composite anode may have a crystallite size to particle size (nm:nm) ratio of about 1:300 to about 1:1. For example, the crystallite size to particle size ratio may be about 1:300 to about 1:200, about 1:300 to about 1:100, about 1:300 to about 1:50, about 1:300 to about 1:20, about 1:300 to about 1:10, about 1:300 to about 1:5, about 1:300 to about 1:2, about 1:300 to about 1:1, about 1:300 to about 2:1, about 1:300 to about 5:1, about 1:300 to about 10:1, about 1:300 to about It may be about 20:1, about 1:300 to about 50:1, about 1:200 to about 50:1, about 1:100 to about 50:1, about 1:50 to about 50:1, about 1:20 to about 50:1, about 1:10 to about 50:1, about 1:5 to about 50:1, about 1:2 to about 50:1, about 1:1 to about 50:1, about 2:1 to about 50:1, about 5:1 to about 50:1, about 10:1 to about 50:1, or about 20:1 to about 50:1. The ratio of crystallite size to particle size may be about 1:300, 1:250, 1:200, 1:150, 1:100, 1:90, 1:80, 1:70, 1:60, 1:50, 1:40, 1:30, 1:20, 1:10, 1:5, 1:2, or about 1:1. In an exemplary embodiment, the ratio of crystallite size to particle size is about 1:18. In another exemplary embodiment, the ratio of crystallite size to particle size is about 13:50 (i.e., about 1:3.85).
[0062] The silicon in the composite anode has a surface area to particle size ratio (m 2For example, the ratio of surface area to particle size may be about 1:300 to about 1:200, about 1:300 to about 1:100, about 1:300 to about 1:50, about 1:300 to about 1:20, about 1:300 to about 1:10, about 1:300 to about 1:5, about 1:300 to about 1:2, about 1:300 to about 1:1, about 1:300 to about 10:10, about 1:300 to about 20:10, about 1:300 to about 30:10, about 1:300 to about 40:10, about 1 The ratio may be from about 1:300 to about 50:10, from about 1:200 to about 50:10, from about 1:100 to about 50:10, from about 1:50 to about 50:10, from about 1:20 to about 50:10, from about 1:10 to about 50:10, from about 1:5 to about 50:10, from about 1:2 to about 50:10, from about 1:1 to about 50:10, from about 10:110 to about 50:10, from about 20:10 to about 50:10, from about 30:10 to about 50:10, or from about 40:10 to about 50:1. The surface area to particle size ratio may be about 1:300, 1:250, 1:200, 1:150, 1:100, 1:90, 1:80, 1:70, 1:60, 1:50, 1:40, 1:30, 1:20, 1:10, 1:5, 1:2, 1:1, 10:10, 20:10, 30:10, 40:10, or about 50:10. In an exemplary embodiment, the surface area to particle size ratio is about 1:5. In another exemplary embodiment, the surface area to particle size ratio is about 1:18.
[0063] The anode active material may be present in the composite anode in an amount of about 30% to about 98% by weight of the composite anode. In some embodiments, the anode active material may be present in an amount of about 30% to about 35%, about 30% to about 40%, about 30% to about 45%, about 30% to about 50%, about 30% to about 55%, about 30% to about 60%, about 30% to about 65%, about 30% to about 70%, about 30% to about 75%, about 30% to about 80%, about 30% to about 85%, about 30% to about 90%, about 30% to about 95%, about 30% to about 98%, about 40% to about 98%, about 45% to about 98%, about 50% to about 55%, about 50% to about 55%, about 50% to about 60%, about 50% to about 65%, about 50% to about 70%, about 50% to about 75%, about 50% to about 80%, about 50% to about 85%, about 50% to about 90%, about 50% to about 95%, about 50% to about 98 ... The catalyst may be present in the composite anode in an amount of about 8%, about 50% to about 98%, about 55% to about 98%, about 60% to about 98%, about 65% to about 98%, about 70% to about 98%, about 75% to about 98%, about 80% to about 98%, 85% to about 98%, about 90% to about 98%, about 40% to about 90%, about 40% to about 80%, about 40% to about 70%, about 40% to about 60%, about 40% to about 55%, about 40% to about 50%, or about 40% to about 45% by weight.
[0064] In other embodiments, the anode active material may be present in the composite anode in an amount of about 40% by weight or greater. In some aspects, the anode active material may be present in the composite anode in an amount of about 40% by weight to about 80% by weight, about 40% by weight to about 75% by weight, about 40% by weight to about 70% by weight, about 40% by weight to about 65% by weight, or about 40% by weight to about 60% by weight. In some examples, the anode active material is present in the composite anode in an amount of about 50% by weight to about 60% by weight.
[0065] The anode active material may include an oxide layer that forms on the outside of the anode active material. This oxide layer typically forms when the anode active material is in contact with air. The oxide layer may have a thickness of about 3 nm to about 5 nm. The oxide layer may passivate the surface from further reaction with air.
[0066] Currently, the operation of electrochemical cells, including solid-state batteries, involves applying stack pressure to the battery during charging and discharging. Stack pressure, sometimes also called force, involves applying pressure to the cell to maintain contact between the respective electrodes and the solid electrolyte. The first cell cycle includes a 100% depth of discharge (DoD), meaning that the cell is fully charged and then fully discharged. The conditioning cycle includes a DoD of less than 100%, for example, less than 90%, less than 80%, less than 70%, less than 60%, less than 50%, less than 40%, less than 30%, less than 20%, or less than 10%. In a series of conditioning cycles, there may be two or more conditioning cycles. The DoD in each of the series of conditioning cycles may be equal or may differ between each of the conditioning cycles. The first cycle or series of conditioning cycles may be part of a formation process before using the battery to power a device. The voltage for each of the series of conditioning cycles may be constant, or in some embodiments the voltage may be increased for each of the conditioning cycles.
[0067] The stack pressure applied during the first cell cycle or series of conditioning cycles may be from about 100 psi to about 2500 psi. In some embodiments, the stack pressure applied during the first cell cycle or series of conditioning cycles may be from about 100 psi to about 500 psi, from about 500 psi to about 1000 psi, from about 1000 psi to about 1500 psi, from about 1500 psi to about 2000 psi, from about 2000 psi to about 2500 psi, from about 100 psi to about 1000 psi, from about 100 psi to about 1500 psi, from about 100 psi to about 2000 psi, from about 500 psi to about 2500 psi, from about 1000 psi to about 2500 psi, from about 1500 psi to about 2500 psi, from about 500 psi to about 2000 psi, or from about 1000 psi to about 2000 psi. In some embodiments, the stack pressure applied during the first cell cycle or series of conditioning cycles may be greater than 2500 psi. In an exemplary embodiment, the stack pressure applied during the first cell cycle or series of conditioning cycles is about 1500 psi. In another exemplary embodiment, the stack pressure applied during the first cell cycle or series of conditioning cycles is about 300 psi.
[0068] The stack pressure may be less than about 300 psi. In some embodiments, the stack pressure can be less than about 300 psi, less than about 250 psi, less than about 200 psi, less than about 150 psi, less than about 100 psi, less than about 50 psi, less than about 25 psi, or less than about 10 psi.
[0069] In some embodiments, the stack pressure may remain constant throughout the life of the electrochemical cell. In other embodiments, the stack pressure may be reduced or increased after one or more cell cycles. In an exemplary embodiment, the stack pressure may remain constant at 1500 psi throughout the life of the electrochemical cell. In another exemplary embodiment, the stack pressure may be about 1500 psi during the first cell cycle, and then the stack pressure is reduced to 300 psi for the remaining life of the electrochemical cell.
[0070] In one embodiment, the anode active material is selected from the group consisting of tin (Sn), germanium (Ge), graphite, hard carbon (e.g., amorphous carbon), Li4Ti5O 12 The anode active material may further comprise one or more materials such as LTO, other known anode active materials, and combinations thereof.
[0071] In some embodiments, the composite anode may optionally further include one or more conductive additives. The conductive additives help distribute the charge density evenly across the anode. The conductive additives may include metal powders, fibers, filaments, or any other materials known to conduct electrons. In some aspects, the one or more conductive additives may include one or more conductive carbon materials, such as carbon fibers, graphite, graphene, carbon black, conductive carbon, amorphous carbon, VGCF, silicon-carbon composites, and carbon nanotubes.
[0072] In some embodiments, the conductive additive may be present in the composite anode in an amount of about 0% to about 15% by weight of the composite anode. In some aspects, the conductive additive may be present in the composite anode in an amount of about 0% to about 10% by weight of the composite anode, or about 0% to about 5% by weight of the composite anode. In some additional aspects, the conductive additive may be present in the composite anode in an amount of about 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or about 15% by weight of the composite anode. In an exemplary embodiment, the conductive additive is present in the composite anode in an amount of about 0% to about 5% by weight of the composite anode. In other embodiments, the conductive additive may be present in the composite anode in an amount between about 0% and about 20% by weight, between about 0% and about 30% by weight, between about 0% and about 40% by weight, between about 0% and about 50% by weight, or between about 0% and about 60% by weight.
[0073] In some embodiments, the average particle size of the conductive additive may be about 5 nm to about 100 nm. In some aspects, the average particle size of the conductive additive may be about 5 nm to about 10 nm, about 5 nm to about 20 nm, about 5 nm to about 30 nm, about 5 nm to about 40 nm, about 5 nm to about 50 nm, about 5 nm to about 60 nm, about 5 nm to about 70 nm, about 5 nm to about 80 nm, about 5 nm to about 90 nm, about 10 nm to about 100 nm, about 20 nm to about 100 nm, about 30 nm to about 100 nm, about 40 nm to about 100 nm, about 50 nm to about 100 nm, about 60 nm to about 100 nm, about 70 nm to about 100 nm, about 80 nm to about 100 nm, about 90 nm to about 100 nm, about 10 nm to about 50 nm, or about 20 nm to about 40 nm. In some examples, the conductive additive may have a particle size of about 30 nm.
[0074] In some embodiments, the composite anode may further optionally include one or more solid electrolyte materials. The solid electrolyte materials, together with the conductive additive, help to distribute the charge density uniformly across the anode. The one or more solid electrolyte materials may include oxides, oxysulfides, sulfides, halides, nitrides, or any other solid electrolytes known in the art. In some preferred embodiments, the one or more solid electrolyte materials may include sulfide solid electrolyte materials, i.e., solid electrolytes having at least one sulfur component. In some embodiments, one or more solid electrolytes may include one or more combinations of materials, such as, for example, Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-LiI-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-S-SiS2-LiCl, Li2S-S-SiS2-B2S3-LiI, Li2S-S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n(where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-S-SiS2-Li3PO4, and Li2S-S-SiS2-Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In) may be included.
[0075] In another embodiment, the solid electrolyte material is Li3PS4, Li4P2S6, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 may be one or more of them. In a further embodiment, the solid electrolyte may be one or more of Li6PS5Cl, Li6PS5Br, Li6PS5I, or may be represented by the formula Li 7-y PS 6-y X y , where "X" represents at least one halogen and / or at least one pseudohalogen, 0 < y ≤ 2.0, the halogen may be one or more of F, Cl, Br, I, and the pseudohalogen may be one or more of N, NH, NH2, NO, NO2, BF4, BH4, AlH4, CN, and SCN. In yet another embodiment, the solid electrolyte material is of the formula Li 8-y-z P2S 9-y-z X y W z (where "X" and "W" represent at least one halogen and / or at least one pseudohalogen, where 0 ≤ y ≤ 1 and 0 ≤ z ≤ 1), the halogen may be one or more of F, Cl, Br, I, and the pseudohalogen may be one or more of N, NH, NH2, NO, NO2, BF4, BH4, AlH4, CN, and SCN.
[0076] In some embodiments, the solid electrolyte material may be present in the composite anode in an amount of about 0% to about 60% by weight of the composite anode, for example, the solid electrolyte may be present in the composite anode in an amount of about 0% to about 10% by weight, about 0% to about 20% by weight, about 0% to about 30% by weight, about 0% to about 40% by weight, about 0% to about 50% by weight, about 10% to about 60% by weight, about 20% to about 60% by weight, about 30% to about 60% by weight, about 40% to about 60% by weight, or about 50% to about 60% by weight. In some embodiments, the solid electrolyte material may be present in the composite anode in an amount of about 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60% by weight of the composite anode. In an exemplary embodiment, the solid electrolyte material is present in an amount of about 35% to about 45% by weight of the composite anode.
[0077] The composite anode may further include a binder. The binder aids in the adhesion of the composite anode to the current collector and provides the composite anode with the structural integrity necessary to resist crack formation while bringing the components of the composite close enough to ensure electron / ion mobility. The binder may also form a flexible matrix when mixed with the solid electrolyte material. The binder may further suspend the silicon active material and conductive additive in the electrolyte matrix, allowing the electrode layer to maintain interparticle contact while the silicon material expands and contracts. In some embodiments, the binder may contain a fluororesin as a structural unit, including vinylidene fluoride (VdF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE), and derivatives thereof. In some additional embodiments, the binder may include homopolymers such as polyvinylidene fluoride (PVdF), polyhexafluoropropylene (PHFP), and binary copolymers such as copolymers of VdF and HFP, such as poly(vinylene difluoride-hexafluoropropylene) copolymer (PVdF-HFP). In another embodiment, the binder may be one or more thermoplastic elastomers, such as, but not limited to, styrene-butadiene rubber (SBR), styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene block copolymer (SIS), styrene-ethylene-butylene-styrene block copolymer (SEBS), polyacrylonitrile (PAN), nitrile-butylene rubber (NBR), polybutadiene, polyisoprene, poly(methacrylate) nitrile-butadiene rubber (PMMA-NBR), ethylene propylene diene monomer rubber (EPDM), and the like.
[0078] In further embodiments, the binder may include one or more acrylic resins, such as, but not limited to, polymethyl methacrylate, polymethyl acrylate, polyethyl methacrylate, polyethyl acrylate, polyisopropyl (meth)acrylate, polyisobutyl (meth)acrylate, polybutyl (meth)acrylate, and the like. In yet another embodiment, the binder may be one or more polycondensation polymers, such as, but not limited to, polyurea, polyamide paper, polyimide, polyester, and the like. In yet a further embodiment, the binder may include one or more nitrile rubbers, such as, but not limited to, acrylonitrile-butadiene rubber (ABR), polystyrene nitrile-butadiene rubber (PS-NBR), and mixtures thereof.
[0079] In a preferred embodiment, the binder can include a styrenic block copolymer. In an exemplary embodiment, the binder can include SEBS. In another exemplary embodiment, the binder includes SEBS and SBS.
[0080] In some embodiments, the binder may be present in the composite anode in an amount of about 0% to about 20% by weight of the composite anode, for example, the binder may be present in the composite anode in an amount of about 0% to about 5% by weight, about 0% to about 10% by weight, about 0% to about 15% by weight, about 5% to about 20% by weight, about 10% to about 20% by weight, or about 15% to about 20% by weight. In an exemplary embodiment, the binder is present in the composite anode in an amount of about 4% to about 5% by weight. In another exemplary embodiment, the binder is present in the composite anode in an amount of about 2% by weight.
[0081] A solid electrochemical cell including a composite anode, a cathode layer, and a solid electrolyte layer (i.e., a separator layer) of the present disclosure is further provided herein. The solid electrolyte layer is disposed between the composite anode and the cathode layer. In some embodiments, the solid electrochemical cell further includes a first current collector layer and a second current collector layer, the first current collector layer is disposed adjacent to the composite anode, and the second current collector layer is disposed adjacent to the cathode layer.
[0082] Preferably, the composite anode of the electrochemical cell contains less than 10 wt% Li 15 Si4 after lithiation. For example, the composite anode of the present disclosure contains less than 10 wt% Li 15 Si4, less than 9 wt% Li 15 Si4, less than 8 wt% Li 15 Si4, less than 7 wt% Li15Si4, less than 6 wt% Li 15 Si4, less than 5 wt% Li 15 Si4, less than 4 wt% Li 15 Si4, less than 3 wt% Li 15 Si4, less than 2 wt% Li 15 Si4, or less than 1 wt% Li 15 Si4 may be included.
[0083] The cathode layer can include a cathode active material and can have, for example, the following: Li(Ni a Co b Mn c )O2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1) or, for example, NMC 111 (LiNi 0.33 Mn 0.33 Co 0.33 O2), NMC 433 (LiNi 0.4 Mn 0.3 Co 0.3 O2), NMC 532 (LiNi 0.5 Mn 0.3 Co 0.2 O2), NMC 622 (LiNi 0.6 Mn 0.2 Co 0.2 O2), NMC 811 (LiNi 0.8 Mn0.1 Co 0.1 Nickel-manganese-cobalt (``NMC'') that can be represented as Ni-Mn-Co or combinations thereof. In another embodiment, the cathode active material may include one or more coated or uncoated metal oxides, such as, but not limited to, V2O5, V6O 13 , MoO3, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1-Y Co Y O2, LiCo 1-Y Mn Y O2, LiNi 1-Y Mn Y O2 (0 ≦ Y < 1), Li (Ni a Co b Mn c )O4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-Z Ni Z O4, LiMn 2-Z Co Z O4 (0 < Z < 2), LiCoPO4, LiFePO4, CuO, Li (Ni a Co b Al c )O2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1) or combinations thereof, etc. may be included. In yet another embodiment, the cathode active material may include one or more coated or uncoated metal sulfides, such as, but not limited to, titanium sulfide (TiS2), molybdenum sulfide (MoS2), iron sulfide (FeS, FeS2), copper sulfide (CuS), and nickel sulfide (Ni3S2), or combinations thereof, etc. may be included. In another embodiment, the cathode active material may include one or more metal fluorides, such as, but not limited to, iron fluoride (FeF2, FeF3), copper fluoride (CuF2), zinc fluoride (ZnF2), titanium fluoride (TiF4), and nickel fluoride (NiF2), etc. may be included.
[0084] The cathode layer may include one or more conductive additives. The conductive additives may include metal powders, fibers, filaments, or any other materials known to conduct electrons. In some embodiments, the one or more conductive additives may include one or more conductive carbon materials, such as carbon fibers, graphite, graphene, carbon black, conductive carbon, amorphous carbon, VGCF, silicon-carbon composites, and carbon nanotubes. In some embodiments, the conductive additives may be present in the cathode layer in an amount of about 1% to about 10%.
[0085] The cathode layer may include one or more solid electrolytes. The one or more solid electrolytes may include an oxide, an oxysulfide, a sulfide, a halide, a nitride, or any other solid electrolyte known in the art. In some preferred embodiments, the one or more solid electrolytes may include a sulfide solid electrolyte. In some embodiments, the solid electrolyte is Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-Li2I-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-S-SiS2-LiCl, Li2S-S-SiS2-B2S3-LiI, Li2S-S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-S-SiS2-Li3PO4, and Li2S-S-SiS2-Li x MO y where x and y are positive numbers and M is P, Si, Ge, B, Al, Ga, or In. In another embodiment, the solid electrolyte comprises a combination of one or more of Li3PS4, Li4P2S6, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12One or more of them may be used. In a further embodiment, the solid electrolyte may be one or more of Li6PS5Cl, Li6PS5Br, Li6PS5I, or may be of the formula Li 7-y PS 6-y X y (wherein, "X" represents at least one halogen and / or at least one pseudohalogen, 0 < y ≦ 2.0, at least one halogen may be one or more of F, Cl, Br, I, and at least one pseudohalogen may be one or more of N, NH, NH2, NO, NO2, BF4, BH4, AlH4, CN, and SCN). In yet another embodiment, the solid electrolyte is of the formula Li 8-y-z P2S 9-y-z X y W z (wherein, "X" and "W" represent at least one halogen element and / or pseudohalogen, in the formula, 0 ≦ y ≦ 1 and 0 ≦ z ≦ 1), the halogen may be one or more of F, Cl, Br, I, and the pseudohalogen may be one or N, NH, NH2, NO, NO2, BF4, BH4, AlH4, CN, and SCN. In some embodiments, the solid electrolyte may be present in the cathode layer in an amount of about 5% to about 20%.
[0086] The cathode layer may include one or more binders. In some embodiments, the binder may include a fluororesin as a structural unit, such as vinylidene fluoride (VdF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE), and derivatives thereof. Specific examples include homopolymers such as polyvinylidene fluoride (PVdF), polyhexafluoropropylene (PHFP), polytetrafluoroethylene (PTFE), binary copolymers such as copolymers of VdF and HFP, such as poly(vinylene difluoride-hexafluoropropylene) copolymers (PVdF-HFP), and the like. In another embodiment, the binder may be one or more thermoplastic elastomers, such as, but not limited to, styrene-butadiene rubber (SBR), styrene-butadiene-styrene copolymer (SBS), styrene-isoprene block copolymer (SIS), styrene-ethylene-butylene-styrene (SEBS), polyacrylonitrile (PAN), nitrile-butylene rubber (NBR), polybutadiene, polyisoprene, poly(methacrylate)nitrile-butadiene rubber (PMMA-NBR), and the like. In a further embodiment, the binder may be one or more acrylic resins, such as, but not limited to, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polyisopropyl (meth)acrylate, polyisobutyl (meth)acrylate, polybutyl (meth)acrylate, and the like. In yet another embodiment, the binder may be one or more polycondensation polymers, such as, but not limited to, polyurea, polyamide paper, polyimide, polyester, and the like. In still further embodiments, the binder may be one or more nitrile rubbers, such as, but not limited to, acrylonitrile-butadiene rubber (ABR), polystyrene nitrile-butadiene rubber (PS-NBR), ethylene propylene diene monomer rubber (EPDM), and mixtures thereof. In some aspects, the binder may be present in the cathode layer in an amount of about 0% to about 5%.
[0087] The electrolyte layer (also referred to herein as "separator layer") may include one or more solid electrolytes. The one or more solid electrolytes may include an oxide, oxysulfide, sulfide, halide, nitride, or any other solid electrolyte known in the art. In some preferred embodiments, the one or more solid electrolytes may include a sulfide solid electrolyte. In some embodiments, the one or more sulfide solid electrolytes are selected from the group consisting of Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-GeS2, Li2S-P2S-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-Li2O-LiBr, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-S-SiS2-LiCl, Li2S-S-SiS2-B2S3-LiI, Li2S-S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2-SS-SiS2-Li3PO4, and Li2S-SiS2-Li x MO y In some embodiments, the one or more solid electrolyte materials may include one or more combinations of materials such as Li3PS4, Li4P2S6, Li7P3S, Li4P2S, Li5P3S, Li6P3S, Li7P3S, Li8P3S, Li9P3S, Li10P3S, Li11P3S, Li12P3S, Li13P3S, Li14P3S, Li15P3S, Li16P3S, Li17P3S, Li18P3S, Li19 ... 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 In another embodiment, the one or more solid electrolyte materials may be of the formula Li6PS5Cl, Li6PS5Br, Li6PS5I, or Li 7-y P.S. 6-y X yIt can be represented by the formula, where "X" represents at least one halogen and / or at least one pseudohalogen, where 0 < y ≦ 2.0, the halogen can be one or more of F, Cl, Br, I, and combinations thereof, and the pseudohalogen can be one or more of N, NH, NH2, NO, NO2, BF4, BH4, AlH4, CN, SCN, and combinations thereof. In another embodiment, one or more solid electrolyte materials have the formula Li 8-y-z P2S 9-y-z X y W z (where "X" and "W" represent at least one halogen and / or at least one pseudohalogen, where 0 ≦ y ≦ 1 and 0 ≦ z ≦ 1), the halogen can be one or more of F, Cl, Br, I, and the pseudohalogen can be one or more of N, NH, NH2, NO, NO2, BF4, BH4, AlH4, CN, SCN, and combinations thereof.
[0088] The electrolyte layer may further include one or more binders. In some embodiments, the binder may include a fluororesin as a structural unit, such as vinylidene fluoride (VdF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE), and derivatives thereof. Specifically, the binder may include homopolymers such as polyvinylidene fluoride (PVdF), polyhexafluoropropylene (PHFP), and polytetrafluoroethylene (PTFE), and binary copolymers such as copolymers of VdF and HFP, such as poly(vinylene difluoride-hexafluoropropylene) copolymer (PVdF-HFP). In another embodiment, the binder may be one or more thermoplastic elastomers, such as, but not limited to, styrene-butadiene rubber (SBR), styrene-butadiene-styrene copolymer (SBS), styrene-isoprene block copolymer (SIS), styrene-ethylene-butylene-styrene (SEBS), polyacrylonitrile (PAN), nitrile-butylene rubber (NBR), polybutadiene, polyisoprene, poly(methacrylate)nitrile-butadiene rubber (PMMA-NBR), and the like. In a further embodiment, the binder may be one or more acrylic resins, such as, but not limited to, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polyisopropyl (meth)acrylate, polyisobutyl (meth)acrylate, polybutyl (meth)acrylate, and the like. In yet another embodiment, the binder may be one or more polycondensation polymers, such as, but not limited to, polyurea, polyamide paper, polyimide, polyester, and the like. In still further embodiments, the binder may be one or more nitrile rubbers, such as, but not limited to, acrylonitrile-butadiene rubber (ABR), polystyrene nitrile-butadiene rubber (PS-NBR), ethylene propylene diene monomer rubber (EPDM), and mixtures thereof. In some aspects, the binder may be present in the electrolyte layer in an amount of about 0% to about 20% by weight.
[0089] In some embodiments, the electrolyte layer can have a thickness of about 10 μm to about 40 μm. In some aspects, the electrolyte layer can have a thickness of about 10 μm to about 20 μm, about 10 μm to about 30 μm, about 20 μm to about 30 μm, about 20 μm to about 40 μm, or about 30 μm to about 40 μm. In some additional embodiments, the electrolyte layer can have a thickness of about 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm, or about 40 μm.
[0090] The first and second current collectors may include one or more of copper, aluminum, nickel, titanium, stainless steel, magnesium, iron, zinc, indium, germanium, silver, platinum, or gold. The current collectors may further include a carbon coating adjacent to the composite anode or cathode layer. In some embodiments, the first or second current collectors may have a thickness of about 5 μm to about 10 μm. In a preferred embodiment, the first current collector includes copper, nickel, and / or steel.
[0091] In general, when a higher stack pressure is applied during the first cell cycle, the electrochemical cell may have a greater capacity retention compared to an electrochemical cell in which a lower stack pressure is applied during the first cell cycle.
[0092] The specific capacity of the cathode layer of the electrochemical cell decreases after each charge / discharge cycle, but the decrease in the specific capacity of the cathode layer of the electrochemical cell of the present disclosure is reduced compared to the electrochemical cell using microscale silicon.In some embodiments, the cathode layer of the electrochemical cell of the present disclosure can have a specific capacity of more than 100mAh / g for at least 100 cycles.For example, the cathode layer of the electrochemical cell can have a specific capacity of more than 100mAh / g for 100 cycles, 150 cycles, 200 cycles, 250 cycles, 300 cycles, 400 cycles, 500 cycles, 600 cycles, 700 cycles, 800 cycles, or more than 800 cycles.
[0093] In some embodiments, the electrochemical cells of the present disclosure have increased capacity retention compared to cells having composite anodes comprising microscale silicon. In some embodiments, the electrochemical cells may have a capacity retention of about 80% or more after 100 or more cycles, for example, the electrochemical cells may have a capacity retention of about 80% or more after about 100 cycles (cycles), 200 cycles, 300 cycles, 400 cycles, 500 cycles, 600 cycles, 700 cycles, 800 cycles, 900 cycles, 1000 cycles, or more than about 1000 cycles.
[0094] In some embodiments, an electrochemical cell of the present disclosure includes a current collector and a composite anode, the composite anode including silicon or an alloy thereof, at least one solid electrolyte material, and at least one binder material, and further, there is no physical separation or lift-off between the current collector and the composite anode in the electrochemical cell after 5 or more cycles, e.g., 10 cycles, 25 cycles, 50 cycles, 75 cycles, 100 cycles, 200 cycles, 300 cycles, 400 cycles, 500 cycles, 600 cycles, 700 cycles, 800 cycles, 900 cycles, 1000 cycles, or greater than about 1000 cycles.
[0095] Also provided herein is a method for preparing composite anode for use in solid electrochemical cell.The method includes: a) combining silicon or its alloy, at least one solid electrolyte material and at least one binder material; b) mixing silicon or its alloy, at least one solid electrolyte material and at least one binder material to form composite mixture; c) adding solvent to composite mixture to form slurry; d) casting the slurry on substrate; and e) drying the slurry to form composite anode;
[0096] In some embodiments, the solvent may be selected from, but is not limited to, one or more of aprotic hydrocarbons, esters, ethers, nitriles, or combinations thereof. In another aspect, the aprotic hydrocarbon may be selected from, but is not limited to, xylene, toluene, benzene, methylbenzene, hexane, heptane, octane, alkanes, isoparaffinic hydrocarbons, or combinations thereof. In another aspect, the ester may be selected from, but is not limited to, one of butyl butyrate, isobutyl isobutyrate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, or combinations thereof. In another aspect, the ether may be selected from, but is not limited to, one of diethyl ether, dibutyl ether, benzyl ether, or combinations thereof. In another aspect, the nitrile may be selected from, but is not limited to, one of acetonitrile, propionitrile, butyronitrile, pyrrolidine, or combinations thereof.
[0097] After the composite anode is dried on the substrate, the anode is densified to increase the density of the composite anode. Methods of densification are well known to those skilled in the art. In a preferred embodiment, densification is achieved by calendaring or pressing, for example, using a linear press. In some embodiments, the temperature during densification may be from about 80° C. to about 140° C. It will be understood that the density of the composite anode depends on the formulation of the composite anode and the densification conditions. Without wishing to be bound by theory, it is believed that increasing the density of the composite anode reduces the porosity of the composite anode, thereby improving interparticle contact and lowering the resistance of the composite anode.
[0098] In some embodiments, the density of the composite anode after densification is about 1 g / cm 3 ~Approx. 1.75g / cm 3 For example, the density of the composite anode after densification may be about 1 g / cm 3 , 1.05g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 , or about 1.75 g / cm 3 In another example, the density of the composite anode after densification may be about 1 g / cm 3 ~Approx. 1.1g / cm 3 , about 1g / cm 3 ~Approx. 1.2g / cm 3 , about 1g / cm 3 ~Approx. 1.3g / cm 3 , about 1g / cm 3 ~ approx. 1.4g / cm 3 , about 1g / cm 3~Approx. 1.5g / cm 3 , about 1g / cm 3 ~Approx. 1.6g / cm 3 , about 1g / cm 3 ~Approx. 1.7g / cm 3 , about 1.1g / cm 3 ~Approx. 1.75g / cm 3 , about 1.2g / cm 3 ~Approx. 1.75g / cm 3 , about 1.3g / cm 3 ~Approx. 1.75g / cm 3 , about 1.4g / cm 3 ~Approx. 1.75g / cm 3 , about 1.5g / cm 3 ~Approx. 1.75g / cm 3 , about 1.6g / cm 3 ~Approx. 1.75g / cm 3 , about 1.7g / cm 3 ~Approx. 1.75g / cm 3 , it can be.
[0099] The composite anode can have a porosity of about 25% to about 50%. In some embodiments, the composite anode can have a porosity of about 25% to about 30%, about 25% to about 35%, about 25% to about 40%, about 25% to about 45%, about 25% to about 50%, about 30% to about 50%, about 35% to about 50%, about 40% to about 50%, or about 45% to about 50%.
[0100] An anode composition comprising an anode active material, a solid electrolyte material, a conductive additive, and a binder, the anode composition having a mass of about 1 g / cm 3 ~Approx. 1.75g / cm 3 Further provided herein is an anode composition having a density of about 100 psi to about 2500 psi. The anode active material, solid electrolyte material, conductive additive, and binder may be selected from any of the materials identified above in this disclosure, and in any of the amounts defined above in this disclosure. In some embodiments, the composition may be subjected to a stack pressure of about 100 psi to about 2500 psi, or greater than 2500 psi.
[0101] In an exemplary embodiment, a composite anode of the present disclosure includes silicon in an amount of about 85% by weight of the composite anode, a conductive additive in an amount of about 10% by weight of the composite anode, and a binder in an amount of about 5% by weight of the composite anode.
[0102] In another exemplary embodiment, the composite anode of the present disclosure includes silicon in an amount between about 48% and about 52% by weight of the composite anode, a binder in an amount between about 2% and about 6% by weight of the composite anode, and a solid electrolyte in an amount between about 44% and about 48% by weight of the composite anode. In a further configuration, the composite anode of the present disclosure includes silicon in an amount between about 50% by weight of the composite anode, a binder in an amount between about 4% by weight of the composite anode, and a solid electrolyte in an amount between about 46% by weight of the composite anode.
[0103] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs.Any method and material similar or equivalent to those described herein can be used in the implementation or testing of the subject matter of this disclosure, but preferred methods and materials are described.For the purpose of this disclosure, the following terms are defined below.
[0104] Concentrations, amounts, and other numerical data may be expressed or presented in a range format herein. It should be understood that such range formats are used merely for convenience and brevity, and should be interpreted flexibly to include not only the numerical values explicitly recited as the limits of the range, but also all individual numerical values or subranges subsumed within the range, as if each numerical value and subrange were explicitly recited. By way of illustration, the numerical range "about 2 to about 50" should be interpreted to include not only the explicitly recited values of 2 to 50, but also all individual values and subranges within the stated range. Thus, included in this numerical range are individual values such as 2, 2.4, 3, 3.7, 4, 5.5, 10, 10.1, 14, 15, 15.98, 20, 20.13, 23, 25.06, 30, 35.1, 38.0, 40, 44, 44.6, 45, 48, etc., as well as subranges such as 1-3, 2-4, 5-10, 5-20, 5-25, 5-30, 5-35, 5-40, 5-50, 2-10, 2-20, 2-30, 2-40, 2-50, etc. This same principle also applies to ranges reciting only one numerical value as a minimum or maximum value. Moreover, such an interpretation should be applied regardless of the breadth of the range or characteristic being described.
[0105] The term "about" is understood by those of ordinary skill in the art and varies to some extent with the context in which it is used. As used herein, when referring to a measurable value such as an amount, duration, etc., the term "about" is meant to encompass a variation of ±10%, including ±5%, ±1%, and ±0.1% from the particular value, where such variation is appropriate for carrying out the disclosed method.
[0106] In this disclosure, the terms "comprises," "comprising," "containing," and "having," etc., can have the meanings ascribed to them in U.S. Patent Law and can mean "includes," "including," etc., and generally, the terms "consisting of" or "consisting of" are closed terms and include only those components, structures, steps, etc. specifically recited in association with such terms, as well as those pursuant to U.S. Patent Law. "Consisting essentially of" or "consisting essentially of" have the meanings generally ascribed to them by U.S. Patent Law. In particular, such terms are generally closed terms, except to allow for the inclusion of additional items, materials, components, steps, or elements that do not materially affect the basic and novel characteristics or function of the item in association with which it is used. For example, trace elements that are present in the composition but do not affect the nature or properties of the composition would be permitted when present in the "consisting essentially of" language, even if they are not explicitly recited in the list of items following such terms. As used herein, where open-ended terms such as "comprising" or "including" are used, it is understood that direct support is given from the terms "consisting essentially of" and "consisting of."
[0107] Exemplary embodiments Embodiment 1: A composite anode for an electrochemical cell, comprising: silicon or an alloy thereof in an amount of at least about 30 wt % of the composite anode; a solid electrolyte material in an amount of about 0 wt % to about 40 wt % of the composite anode; and a binder in an amount of about 0 wt % to about 20 wt % of the composite anode.
[0108] Embodiment 2: The composite anode of embodiment 1, wherein the silicon has a particle size of about 10 nm to about 100 nm.
[0109] Embodiment 3: The composite anode of embodiment 1 or embodiment 2, wherein the silicon has a particle size of about 50 nm to about 80 nm.
[0110] Embodiment 4: The composite anode of any one of embodiments 1 to 3, further comprising a conductive additive in an amount of about 0 wt % to about 15 wt % of the composite anode.
[0111] Embodiment 5: The composite anode of embodiment 4, wherein the conductive additive comprises carbon.
[0112] Embodiment 6: The composite anode of embodiment 4, wherein the conductive additive has a particle size of about 5 nm to about 100 nm.
[0113] Embodiment 7: The composite anode of any one of embodiments 1 to 6, wherein the silicon has a crystallite size of about 1 nm to about 50 nm.
[0114] Embodiment 8: The composite anode of any one of embodiments 1 to 7, wherein the silicon has a crystallite size of about 1 nm to about 20 nm.
[0115] Embodiment 9: Silicon is about 20m 2 9. The composite anode of any one of embodiments 1 to 8, having a surface area of less than 1 / g.
[0116] Embodiment 10: Silicon is about 1 m 2 / g~about 50m 2 9. The composite anode of any one of embodiments 1 to 8, having a surface area of 100 nm / g.
[0117] Embodiment 11: Silicon is about 1 m 2 / g~about 20m 2 11. The composite anode of any one of embodiments 1 to 10, having a surface area of 1 / g.
[0118] Embodiment 12: A composite anode having a coating density of about 1 g / cm 3 ~Approx. 1.75g / cm 3 12. The composite anode of any one of embodiments 1 to 11, having a density of
[0119] Embodiment 13: Tin, germanium, graphite, Li4Ti5O 12 13. The composite anode of any one of embodiments 1 to 12, further comprising an anode active material comprising a zeolite, a hard carbon, or a combination thereof.
[0120] Embodiment 14: The composite anode of any one of embodiments 1 to 13, wherein silicon is present in an amount of about 30% to about 98% by weight of the composite anode.
[0121] Embodiment 15: The composite anode of any one of embodiments 1 to 14, wherein silicon is present in an amount of at least about 40% by weight of the composite anode.
[0122] Embodiment 16: A composite anode for an electrochemical cell comprising: silicon or an alloy thereof in an amount of at least about 30 wt. % of the composite anode; a solid electrolyte material in an amount of about 0 wt. % to about 40 wt. % of the composite anode; and a binder in an amount of about 0 wt. % to about 20 wt. % of the composite anode, wherein the silicon has the following characteristics: a particle size of about 10 nm to about 100 nm; a crystallite size of about 1 nm to about 20 nm; and a binder content of about 100%. 2 / g~about 20m 2 / g of surface area.
[0123] Embodiment 17: Silicon has a crystallite size to surface area (nm:m) ratio of about 1:50 to about 50:1. 2 17. The composite anode of any one of embodiments 1 to 16, having a ratio of (A / g) of 1:1 to 1:1.
[0124] Embodiment 18: The composite anode of any one of embodiments 1 to 17, wherein the silicon has a ratio of crystallite size to particle size (nm:nm) of about 1:300 to about 1:1.
[0125] Embodiment 19: The silicon has a surface area to particle size (m 2 19. The composite anode of embodiments 1 to 18, having a ratio of 1:1 / g:nm.
[0126] Embodiment 20: An electrochemical cell having a composite anode, cathode, and electrolyte layer comprising silicon or an alloy thereof in an amount of at least about 30 wt % of the composite anode, a solid electrolyte material in an amount of about 0 wt % to about 40 wt % of the composite anode, and a binder in an amount of about 0 wt % to about 20 wt % of the composite anode.
[0127] Embodiment 21: The electrochemical cell of embodiment 20, wherein the silicon has a particle size of about 10 nm to about 300 nm.
[0128] Embodiment 22: The electrochemical cell of embodiment 20 or 21, wherein the silicon has a particle size of about 50 nm to about 80 nm.
[0129] Embodiment 23: An electrochemical cell as described in any one of embodiments 20 to 22, wherein the composite anode further comprises a conductive additive in an amount of about 0% to about 15% by weight of the composite anode.
[0130] Embodiment 24: The electrochemical cell of embodiment 23, wherein the conductive additive comprises carbon.
[0131] Embodiment 25: The electrochemical cell of embodiment 23, wherein the conductive additive has a particle size of about 5 nm to about 300 nm.
[0132] Embodiment 26: An electrochemical cell according to any one of embodiments 20 to 25, wherein the silicon has a crystallite size of about 1 nm to about 50 nm.
[0133] Embodiment 27: An electrochemical cell according to any one of embodiments 20 to 26, wherein the silicon has a crystallite size of about 1 nm to about 20 nm.
[0134] Embodiment 28: Silicon is about 20 m 228. An electrochemical cell as described in any one of embodiments 20 to 27, having a surface area of less than 1 / g.
[0135] Embodiment 29: Silicon is about 1 m 2 / g~about 50m 2 28. An electrochemical cell as described in any one of embodiments 20 to 27, having a surface area of 1 / g.
[0136] Embodiment 30: Silicon is about 1 m 2 / g~about 20m 2 30. An electrochemical cell as described in any one of embodiments 20 to 29, having a surface area of 1 / g.
[0137] Embodiment 31: A composite anode having a coating density of about 1 g / cm 3 ~Approx. 1.75g / cm 3 31. The electrochemical cell of any one of embodiments 20 to 30, having a density of
[0138] Embodiment 32: Tin, germanium, graphite, Li4Ti5O 12 32. The electrochemical cell of any one of embodiments 20-31, further comprising an anode active material comprising a zeolite, a hard carbon, or a combination thereof.
[0139] Embodiment 33: An electrochemical cell as described in any one of embodiments 20 to 32, wherein silicon is present in an amount of about 30% to about 98% by weight of the composite anode.
[0140] Embodiment 34: An electrochemical cell as described in any one of embodiments 20 to 33, wherein silicon is present in an amount of at least about 40% by weight of the composite anode.
[0141] Embodiment 35: An electrochemical cell according to any one of embodiments 20 to 34, wherein the cathode comprises a conductive additive.
[0142] Embodiment 36: The electrochemical cell of any one of embodiments 20 to 35, wherein the cathode comprises a solid electrolyte.
[0143] Embodiment 37: The electrochemical cell of any one of embodiments 20 to 36, wherein the cathode comprises a cathode active material.
[0144] Embodiment 38: The electrochemical cell of any one of embodiments 20 to 37, wherein the cathode comprises a binder.
[0145] Embodiment 39: The electrochemical cell of any one of embodiments 20 to 38, wherein the electrolyte layer comprises a solid electrolyte.
[0146] Embodiment 40: The electrochemical cell of any one of embodiments 20-39, wherein the electrolyte layer comprises a binder.
[0147] Embodiment 41: An electrochemical cell according to any one of embodiments 20 to 40, wherein the electrolyte layer is disposed between the composite anode and the cathode.
[0148] Embodiment 42: The electrochemical cell of any one of embodiments 20-41, further comprising a first current collector and a second current collector.
[0149] Embodiment 43: An electrochemical cell as described in embodiment 42, wherein a first current collector is disposed adjacent to the composite anode.
[0150] Embodiment 44: An electrochemical cell as described in embodiment 42, wherein a second current collector is disposed adjacent to the cathode.
[0151] Embodiment 45: A method of preparing a composite anode for an electrochemical cell, comprising combining silicon or an alloy thereof, a solid electrolyte material, and a binder to form a composite mixture; adding a solvent to the composite mixture to form a slurry; casting the slurry on a substrate; and drying the slurry on the substrate to form a composite anode.
[0152] Embodiment 46: The method of embodiment 45, wherein the silicon has a particle size of about 10 nm to about 100 nm.
[0153] Embodiment 47: The method of embodiment 45 or embodiment 46, wherein the silicon has a particle size of about 50 nm to about 80 nm.
[0154] Embodiment 48: The method of any one of embodiments 45 to 47, further comprising a conductive additive in an amount of about 0 wt % to about 15 wt % of the composite anode.
[0155] Embodiment 49: The method of embodiment 48, wherein the conductive additive comprises carbon.
[0156] Embodiment 50: The method of embodiment 48, wherein the conductive additive has a particle size of about 5 nm to about 100 nm.
[0157] Embodiment 51: The method of any one of embodiments 45 to 50, wherein the silicon has a crystallite size of about 1 nm to about 50 nm.
[0158] Embodiment 52: The method of any one of embodiments 45 to 51, wherein the silicon has a crystallite size of about 1 nm to about 20 nm.
[0159]
[0046] Embodiment 53: The silicon has a thickness of about 20 mm. 2 The method of any one of embodiments 45 to 52, having a surface area of less than 1 / g.
[0160] Embodiment 54: Silicon is about 1 m 2 / g~about 50m 2 The method of any one of embodiments 45 to 52, having a surface area of / g.
[0161] Embodiment 55: Silicon is about 1 m 2 / g~about 20m 2 The method of any one of embodiments 45 to 54, having a surface area of 1 / g.
[0162]
[0081] Embodiment 56: A composite anode having a coating density of about 1 g / cm 3 ~Approx. 1.75g / cm 3 56. The method of any one of embodiments 45 to 55, wherein the density is
[0163] Embodiment 57: A composite mixture comprising tin, germanium, graphite, Li4Ti5O 12 57. The method of any one of embodiments 45-56, further comprising an anode active material comprising a carbon nanotube, a hard carbon, or a combination thereof.
[0164] Embodiment 58: The method of any one of embodiments 45 to 57, wherein the silicon is present in an amount of about 30% to about 98% by weight of the composite anode.
[0165] Embodiment 59: The method of any one of embodiments 45 to 58, wherein silicon is present in an amount of at least about 40% by weight of the composite anode.
[0166] Embodiment 60: The method of any one of embodiments 45 to 59, further comprising densifying the composite anode. EXAMPLES
[0167] example Examples are described below for illustrative purposes and to illustrate certain embodiments of the present disclosure.However, the scope of claims is in no way limited by the examples described herein.Various changes and modifications to the disclosed embodiments are obvious to those skilled in the art, and such changes and modifications can be made without departing from the spirit of the present disclosure and the technical scope of the appended claims, including but not limited to those related to the chemical structure, substituents, derivatives, preparations, or techniques of the present disclosure.The definitions of variables in the structures in the schemes herein are equivalent to those of the corresponding positions in the formulas presented herein.
[0168] Example 1: Physical Properties of Silicon Silicon powder was used as obtained from the manufacturer. Particle size information was provided by the supplier. Surface area was measured using nitrogen adsorption on a Quantachrome NOVAtouch Gas Sorption Analyzer using 11-point Brunauer-Emmett-Teller (BET) analysis.
[0169] Scherrer analysis: Powder X-ray diffraction was performed on a Bruker D2 Phaser instrument. Results were obtained with a 30 kV generator and an incident x-ray wavelength of approximately 1.54 Å from Cu-Kα. The Scherrer equation was used: D=κλ / (βcosθ), where κ is a constant from 0.89-1, λ is the wavelength of the incident x-ray, β is the full width at half maximum measured in radians, and θ is the Bragg angle. The range of crystallite sizes for each material type was determined by analyzing the
[0111] ,
[0220] , and
[0311] crystallographic planes, which correspond to approximate 2θ values of 28.45, 47.30, and 56.12 degrees, respectively. The physical properties are summarized in Table 1 below.
[0170] [Table 1]
[0171] Preparation of electrolyte material: Li2S, P2S5, and LiCl were combined in a stoichiometric ratio of 5:1:2 to produce the desired sulfide solid electrolyte. This combination was added to a 500 ml zirconia grinding jar containing zirconia grinding media and xylene as the solvent. The mixture is milled in a Retsch PM 100 planetary mill at 400 RPM for 12 hours. The material was recovered and dried at 70°C in an inert argon environment. The resulting solid electrolyte powder was further heated at 450°C for 2 hours.
[0172] Preparation of the positive electrode: NMC (nickel-manganese-cobalt oxide), Li2S:P2S5:LiCl-based solid electrolyte material, carbon-based conductive additive including a mixture of graphite and carbon black, and binder including PVDF-HFP and SEBS were mixed in a desired ratio in isobutyl isobutyrate (isobutyl isobutyrate). The mixture was then dried and used as the positive electrode material.
[0173] Preparation of Negative Electrodes: Three negative electrodes were prepared and labeled "Example 1", "Comparative Example 1", and "Comparative Example 2".
[0174] Example 1: Particle size of 50-80 nm, 10-20 m 2 A Si material having a surface area of 1000 μg / g and a crystallite size of 10-13 nm was mixed with a Li2S:P2S5:LiCl-based solid electrolyte material, a carbon-based conductive additive including carbon black, and a binder including SEBS in a desired ratio in isobutyl isobutyrate. The mixture was then dried and used as the anode material in Example 1.
[0175] Comparative Example 1: Particle size 50 nm, surface area 70 to 100 m 2 The Si material with 1.0 g / g and crystallite size of 8 nm was mixed with a Li2S:P2S5:LiCl-based solid electrolyte material, a carbon-based conductive additive including carbon black, and a binder including SEBS in a desired ratio in isobutyl isobutyrate. The mixture was then dried and used as the negative electrode material of Comparative Example 1.
[0176] Comparative Example 2: Particle size of 200-300 nm, 6 m 2 A Si material having a surface area of 1000 μg / g and a crystallite size of 34-45 nm was mixed with a Li2S:P2S5:LiCl-based solid electrolyte material, a carbon-based conductive additive, and one or more binders in a desired ratio in one or more solvents. The mixture was then dried and used as the negative electrode material of Comparative Example 2.
[0177] In each of the above examples, silicon was mixed with a solid electrolyte material, a carbon-based conductive additive including carbon black, and a binder including SEBS. Isobutyl isobutyrate was added to the composite mixture to form a slurry with ideal rheological properties (i.e., viscosity and power law behavior) for casting / coating. The slurry was then coated onto a substrate and dried to form a composite anode.
[0178] The composite anode was incorporated into an electrochemical cell with lithium metal as the counter electrode. The cell was cycled from 0.05 V to 1.0 V. The first cycle efficiency was calculated by determining the ratio of the first cycle delithiation capacity of the silicon electrode to the first cycle lithiation capacity of the silicon electrode.
[0179] As can be seen from Figure 1, Comparative Example 1 had small particle size and good cycle stability. However, the high surface area and relatively large surface oxides made casting difficult, lowering the first cycle efficiency (84.5%) and capacity. Comparative Example 2 had a low surface area, which improved the first cycle efficiency (91.2%) and capacity. The silicon of Example 1, combined with the small particle size and low surface area, showed a surprisingly high first cycle efficiency (94.5%), high capacity, and good cycle life.
[0180] Thus, it was observed that particles with small crystallite size but high surface area, or large crystallite size but low surface area, could not be cycled with high capacity and long cycle life. It is the unique structure of small crystallite size with low surface area combined with solid electrolyte that allows near theoretical capacity and long cycle life. Without wishing to be bound by theory, this effect is believed to be due to the fact that the specific surface area of the material is reduced by the Si nanoparticles being connected, thus blocking the access of the electrolyte to the Si at these connection sites, while the specific surface area of the material is reduced by 20m 2 This is believed to be achieved due to the surface area being maintained at less than 1 / g.
[0181] Example 2: Physical Properties of Silicon Additional and comparative composite anodes were prepared. The properties of these compositions are shown in Table 2. Particle size: 100-180 nm, 20-30 m 2 A Si material having a surface area of 1000 μg / g and a crystallite size of 17-20 nm was mixed with a Li2S:P2S5:LiCl-based solid electrolyte material, a carbon-based conductive additive including carbon black, and a binder including SEBS in a desired ratio in isobutyl isobutyrate. The mixture was then dried and used as the negative electrode material in Example 2.
[0182] Comparative Example 3: Particle size of 200-400 nm, 30-40 m 2 A Si material having a surface area of 1000 μg / g and a crystallite size of 30-40 nm was mixed with a Li2S:P2S5:LiCl-based solid electrolyte material, a carbon-based conductive additive including carbon black, and a binder including SEBS in a desired ratio in isobutyl isobutyrate. The mixture was then dried and used as the negative electrode material of Comparative Example 3.
[0183] Comparative Example 4: Particle size of 1000-8000 nm, 4-6 m 2 A Si material having a surface area of 1000 μg / g and a crystallite size of 31-42 nm was mixed with a Li2S:P2S5:LiCl-based solid electrolyte material, a carbon-based conductive additive including carbon black, and a binder including SEBS in a desired ratio in isobutyl isobutyrate. The mixture was then dried and used as the negative electrode material of Comparative Example 4.
[0184] [Table 2]
[0185] The composite anodes were assembled into pouch cells and then cycled at a stack pressure of about 300 psi, a voltage window of 2.5 V to 4.1 V, and a temperature of about 45° C. The silicon content of each anode composition was about 50 wt %. As can be seen from FIG. 2, Example 2 had particle size, crystallite size, and surface area within the desired range and showed similar cycle life performance as Example 1. Comparative Example 3 had crystallite size within the desired range, but the particle size was larger than the materials used in Examples 1 and 2. In addition, the surface area of the material used in Comparative Example 3 was outside the desired range, and therefore a lower total discharge capacity was achieved. The silicon of Example 2 combines small particle size, small surface area, and small crystallite size to show excellent cycle life.
[0186] In another experiment, the composite anode was assembled into a Daicel and cycled at a stack pressure of about 1000 psi, a voltage window of 2.5 V to 4.25 V, and a temperature of 70° C. The silicon content of the composite anode was about 52 wt %. As can be seen from FIG. 3, Comparative Example 4 had a surface area in the desired range, but also had crystallite and particle sizes that spanned the desired range. This resulted in poor cycle life and a rapid decline in discharge capacity.
[0187] The features described above, as well as the features claimed below, may be combined in various ways without departing from the scope of the present specification. It is therefore noted that the matters contained in the above description or shown in the accompanying drawings are to be interpreted as illustrative and not limiting. The above-described embodiments should be considered as examples of the present invention, rather than limiting the scope of the present invention. In addition to the above-described embodiments of the present invention, a review of the detailed description and the accompanying drawings will show that there are other embodiments of such invention. Thus, many combinations, permutations, variations, and modifications of the above-described embodiments of the present invention that are not expressly described herein will nevertheless fall within the scope of such invention. The scope of the appended claims is intended to encompass all descriptions of the general and specific features described herein, as well as the scope of the present methods and systems, which may be said to lie therebetween, as a matter of words.
Claims
1. 1. A composite anode for an electrochemical cell comprising: silicon or an alloy thereof in an amount of at least about 30% by weight of said composite anode; a solid electrolyte material in an amount from about 0% to about 40% by weight of the composite anode; and a binder in an amount of about 0% to about 20% by weight of the composite anode; A composite anode comprising:
2. The composite anode of claim 1 , wherein the silicon has a particle size of about 10 nm to about 300 nm.
3. The composite anode of claim 1 , wherein the silicon has a particle size of about 50 nm to about 80 nm.
4. 10. The composite anode of claim 1, further comprising a conductive additive in an amount of about 0% to about 15% by weight of the composite anode.
5. The composite anode of claim 4 , wherein the conductive additive comprises carbon.
6. The composite anode of claim 4, wherein the conductive additive has a particle size of about 5 nm to about 100 nm.
7. 2. The composite anode of claim 1, wherein the silicon has a crystallite size of about 1 nm to about 50 nm.
8. 2. The composite anode of claim 1, wherein the silicon has a crystallite size of about 1 nm to about 20 nm.
9. The silicon is about 20 m 2 13. The composite anode of claim 1 having a surface area of less than 1.0 W / g.
10. The silicon is about 1 m 2 / g ~ approx. 50m 2 2. The composite anode of claim 1 having a surface area of 1.0 μm / g.
11. The silicon is about 1 m 2 / g ~ approx. 20m 2 2. The composite anode of claim 1 having a surface area of 1.0 μm / g.
12. The composite anode has a thickness of about 1 g / cm 3 ~Approx. 1.75g / cm 3 2. The composite anode of claim 1 having a density of
13. The anode active material further comprises tin, germanium, graphite, Li 4 Ti 5 O 12 10. The composite anode of claim 1 comprising a zeolite, a hard carbon, or a combination thereof.
14. 10. The composite anode of claim 1, wherein the silicon is present in an amount of about 30% to about 98% by weight of the composite anode.
15. 10. The composite anode of claim 1, wherein said silicon is present in at least about 40% by weight of said composite anode.
16. The silicon has a crystallite size to surface area (nm:m) of about 1:50 to about 50:
1. 2 2. The composite anode of claim 1 having a ratio of 0.1 to 0.5 wt.
17. 2. The composite anode of claim 1, wherein the silicon has a ratio of crystallite size to particle size (nm:nm) of about 1:300 to about 1:
1.
18. The silicon has a surface area to particle size (m 2 13. The composite anode of claim 1 having a ratio of 1:1 / g:nm.
19. 1. A composite anode for an electrochemical cell comprising: silicon or an alloy thereof in an amount of at least about 30% by weight of said composite anode; a solid electrolyte material in an amount from about 0% to about 40% by weight of the composite anode; and a binder in an amount of about 0% to about 20% by weight of the composite anode; Including, The silicon has the following characteristics: A particle size of about 10 nm to about 100 nm; A crystallite size of about 1 nm to about 20 nm; and Approximately 1m 2 / g ~ approx. 20m 2 / g surface area having two or more of Composite anode.
20. 1. An electrochemical cell comprising: Composite anode, A cathode, and electrolyte layer Including, The composite anode is silicon or an alloy thereof in an amount of at least about 30% by weight of said composite anode; a solid electrolyte material in an amount from about 0% to about 40% by weight of the composite anode; and a binder in an amount of about 0% to about 20% by weight of the composite anode; 1. An electrochemical cell comprising:
21. 21. The electrochemical cell of claim 20, wherein the silicon has a particle size of about 10 nm to about 100 nm.
22. 21. The electrochemical cell of claim 20, wherein the silicon has a particle size of about 50 nm to about 80 nm.
23. 21. The electrochemical cell of claim 20, wherein the composite anode further comprises a conductive additive in an amount from about 0% to about 15% by weight of the composite anode.
24. 24. The electrochemical cell of claim 23, wherein the conductive additive comprises carbon.
25. 24. The electrochemical cell of claim 23, wherein the conductive additive has a particle size of about 5 nm to about 100 nm.
26. 21. The electrochemical cell of claim 20, wherein the silicon has a crystallite size of about 1 nm to about 50 nm.
27. 21. The electrochemical cell of claim 20, wherein the silicon has a crystallite size of about 1 nm to about 20 nm.
28. The silicon is about 20 m 2 21. The electrochemical cell of claim 20 having a surface area of less than 100 nm / g.
29. The silicon is about 1 m 2 / g ~ approx. 50m 2 21. The electrochemical cell of claim 20 having a surface area of 100 / g.
30. The silicon is about 1 m 2 / g ~ approx. 20m 2 21. The electrochemical cell of claim 20 having a surface area of 100 / g.
31. The composite anode has a thickness of about 1 g / cm 3 ~Approx. 1.75g / cm 3 21. The electrochemical cell of claim 20 having a density of
32. The anode active material further comprises tin, germanium, graphite, Li 4 Ti 5 O 12 21. The electrochemical cell of claim 20, further comprising a zeolite, a hard carbon, or a combination thereof.
33. 21. The electrochemical cell of claim 20, wherein the silicon is present in an amount of about 30% to about 98% by weight of the composite anode.
34. 21. The electrochemical cell of claim 20, wherein the silicon is present in an amount of at least about 40% by weight of the composite anode.
35. 21. The electrochemical cell of claim 20, wherein the cathode comprises a conductive additive.
36. 21. The electrochemical cell of claim 20, wherein the cathode comprises a solid electrolyte.
37. 21. The electrochemical cell of claim 20, wherein the cathode comprises a cathode active material.
38. 21. The electrochemical cell of claim 20 wherein the cathode comprises a binder.
39. 21. The electrochemical cell of claim 20, wherein the electrolyte layer comprises a solid electrolyte.
40. 21. The electrochemical cell of claim 20, wherein the electrolyte layer comprises a binder.
41. 21. The electrochemical cell of claim 20, wherein the electrolyte layer is disposed between the composite anode and the cathode.
42. 21. The electrochemical cell of claim 20 further comprising a first current collector and a second current collector.
43. 43. The electrochemical cell of claim 42, wherein the first current collector is disposed adjacent to the composite anode.
44. 43. The electrochemical cell of claim 42, wherein the second current collector is disposed adjacent to the cathode.
45. 1. A method of making a composite anode for an electrochemical cell, comprising: mixing silicon or an alloy thereof, a solid electrolyte material, and a binder to form a composite mixture; adding a solvent to the composite mixture to form a slurry; casting the slurry onto a substrate; and drying the slurry on the substrate to form the composite anode; A method comprising:
46. 46. The method of claim 45, wherein the silicon has a particle size of about 10 nm to about 100 nm.
47. The method of claim 45, wherein the silicon has a particle size of about 50 nm to about 80 nm.
48. The method of claim 45, further comprising a conductive additive in an amount from about 0% to about 15% by weight of the composite anode.
49. 49. The method of claim 48, wherein the conductive additive comprises carbon.
50. The method of claim 48, wherein the conductive additive has a particle size of about 5 nm to about 100 nm.
51. 46. The method of claim 45, wherein the silicon has a crystallite size of about 1 nm to about 50 nm.
52. 46. The method of claim 45, wherein the silicon has a crystallite size of about 1 nm to about 20 nm.
53. The silicon is about 20 m 2 46. The method of claim 45, wherein the surface area is less than 1 / g.
54. The silicon is about 1 m 2 / g ~ approx. 50m 2 The method of claim 45, having a surface area of 1 / g.
55. The silicon is about 1 m 2 / g ~ approx. 20m 2 The method of claim 45, having a surface area of 1 / g.
56. The composite anode has a thickness of about 1 g / cm 3 ~Approx. 1.75g / cm 3 The method of claim 45, having a density of
57. The composite mixture further includes an anode active material, the anode active material being selected from the group consisting of tin, germanium, graphite, and Li. 4 Ti 5 O 12 , hard carbon, or a combination thereof.
58. The method of claim 45, wherein the silicon is present in an amount of about 30% to about 98% by weight of the composite anode.
59. 46. The method of claim 45, wherein the silicon is present in an amount of at least about 40% by weight of the composite anode.
60. 46. The method of claim 45, further comprising densifying the composite anode.
Citation Information
Patent Citations
Nanoscale silicon particles in negative electrode materials for use in lithium-ion batteries
JP2007534118A
NEGATIVE ELECTRODE ACTIVE MATERIAL FOR SECONDARY BATTERY, METHOD FOR PRODUCING THE SAME, NEGATIVE ELECTRODE FOR SECONDARY BATTERY, SECONDARY BATTERY, AND Si-OXIDE SOLID ELECTROLYTE COMPLEX
JP2014022319A
Amorphous Silicon in Solid Electrolytes, Compositions and Anodes
US20210313562A1
Negative-electrode active material and lithium ion secondary battery using same
WO2017150311A1
Negative electrode material for lithium-ion secondary cells
WO2019131862A1